Customer acceptance and usage of Mobile Hotel Reservation Apps (MHRA): the influence of technology readiness, determinants of UTAUT2, TRUST and M-Satisfaction on post purchase behaviour / Mohd Noor Ismawi Ismail - Ismail, Mohd Noor Ismawi (2023)
Technology acceptance models have been used widely in studies aimed at predicting and explaining the customer’s acceptance and usage of new technologies. However, the limited research focuses on the realm of mobile apps within the hospitality industry. This study examines the customer’s acceptance and usage of Mobile Hotel Reservation Apps (MHRA) by focusing on the aspects of their Technology Readiness (TR), Trust, Mobile Satisfaction (M-Satisfaction) and subsequent behaviour. This study extended the Unified Theory of Acceptance and Use of Technology (UTAUT2) model with the Technology Readiness Index (TRI2.0). A quantitative research method through an online survey was used. The data of 422 respondents were first analysed in SPSS Statistic 22 program, and further empirical analysis was made via SmartPLS 3.0. This study adopted the PLS-SEM analysis. In the first step, the Measurement Model analysis was operationalised to confirm the reliability and validity of the survey instruments. In the second stage, the structural model was utilised to assess the study’s hypotheses. The results from the data analysis of this research confirm that the customers’ state of technology readiness is divided into two groups: motivator and inhibitor. The motivator type of customers possessed a favourable inclination towards the usage of MHRA, while the inhibitor showed a hostile attitude towards acceptance and the usage of MHRA technology. Meanwhile, Effort Expectancy, Facilitating Conditions, Hedonic Motivation and Habit are the main factors influencing their M-Satisfaction. As expected, satisfaction with the MHRA will affect their future behaviour. Another key finding of this study is the mediating effect of mobile satisfaction. This study found that M-Satisfaction mediates the relationship between Effort Expectancy, Social Influence, Hedonic Motivation and Habit towards post-purchase behaviour. In contrast, the remaining determinants were found to be insignificant. This study found customers perceived Trust as an essential predictor between Performance Expectancy, Effort Expectancy, Facilitating Conditions and M-Satisfaction. Overall, this study's findings highlighted the potent factors influencing customers' acceptance of smartphone-based mobile reservation apps within the hotel environment. This significantly contributed to enhancing the body of knowledge within the realm of mobile technology acceptance and benefited the hoteliers by shedding some light on the prospect of investing in mobile hotel apps.